Self healing concrete crack by using pulverized fuel ash (PFA) as cement replacement material - Eddy, Misrum (2010)
Nowadays the high demand of cement is an indication of development especially for the construction industry. Therefore, it is needed an alternative way in fulfill this situation. Many researches were developed in order to find suitable material to be used as a replacement for cement such as palm oil fuel ash and pulverized fuel ash. Pulverized fuel ash can be used as a partial replacement material in cement composition and this material has pozzolana effect that can generate the self healing process. Self healing is an autogenous healing of cracks in concrete is showed by the formation of calcite in the crack. In this study, by product of coal combustion power plant from Tanjung Bin, Johore namely pulverized fuel ash (PFA), was used as the partial replacement in cement in order to study the effectiveness of PFA toward self healing in concrete crack. The ultrasonic pulse velocity (UPV) and compressive strength test were conducted to determine the ability of self healing of concrete containing PFA. The result shows that 20 % of PFA (PFA-20) is the best percentages of cement replacement and water curing was the best mechanism to heal the hairline crack in concrete.